Utility of Oblique Sagittal Reformatted and Three-dimensional Surface Reconstruction Computed Tomography in Foraminal Stenosis Decompression. Issue 1 (December 2018) - Oshina, Masahito; Oshima, Yasushi; Tanaka, Sakae; Tan, Lee; Li, Xudong; Tuchman, Alexander; Riew, K.
Abstract Determining the responsible level of cervical radiculopathy can be difficult. Because asymptomatic findings are common in cervical radiculopathy, diagnoses based on imaging studies can be inaccurate. Therefore, we investigated whether the application of oblique sagittal reformatted computed tomography (oblique sagittal CT) and three-dimensional surface reconstruction CT (3DCT) affects surgical plans for patients with cervical foraminal stenosis and whether it assists diagnosis of foraminal stenosis. Accordingly, four reviewers, with office notes, observed the CT and magnetic resonance imaging (MRI) images of 18 patients undergoing surgical treatment for cervical radiculopathy. After reviewing the MRI and sagittal, coronal, and axial CT images, the reviewers recorded the operation to be performed; they examined oblique sagittal CT and 3DCT images of the same patients and noted any differences from their surgical plans. Consequently, we analyzed these changes in the decompressed foramina in the surgical plan; mean percent change in the plan was 18.1%. Inter-rater reliability improved from κ - 0.194 to κ - 0.240. Therefore, the addition of oblique and 3DCT images improves inter-rater reliability owing to changes in a part of decompressed foramina. The addition of oblique sagittal CT and 3DCT is helpful in evaluating the foramen and planning surgical treatment of cervical radiculopathy.